Strategic design of self-generated Ni-N-C hybrid sites in 3D network structures as counter electrodes in photovoltaics - Genhui Teng; Baorui Liu; Zhe Kang; Yanhui Xie; Dongying Hu; Dawei Zhao (Resources Chemicals and Materials, 2023)
The technical bottleneck of carbon materials as counter electrodes (CEs) lies in their limited electrical conductivity, extended ion diffusion paths, poor dispersion, and high contact resistance. Problem-oriented in-situ self-grown N-doped CNTs-coated Ni nanoparticles based on N-doped carbonaceous structures derived from pitaya peel (PC) are adopted to construct Ni-N-C hybrid 3D ionized network sites (Ni@NCNTs/PC-4) as CEs. Structural characterization, micromorphological and chemical composition analyses revealed the 3D network structure of Ni@NCNTs/PC-4 with abundant active sites. They effectively shorten the diffusion distance of I3− ions with a smaller charge transfer resistance (5.21 Ω) than that of PC (12.53 Ω). DSSCs based on Ni@NCNTs/PC-4 display good optoelectronic properties, in which the short-circuit current density (Jsc) is 13.27 mA/cm2, higher than those of Pt (11.66 mA/cm2) and PC (6.99 mA/cm2). The PCE value (5.13%) of DSSCs based on Ni@NCNTs/PC-4 is also higher than that of DSSCs based on PC (2.47%). Overall, this work provides a preliminary research and new ideas for further in-depth study of biomass-derived 3D structured-carbons that contribute to key electrodes in DSSCs.